Modeling of flexible wheat straw by discrete element method and its parameter calibration - Liu, Fanyi; Zhang, Jian; Chen, Jun (International Journal of Agricultural and Biological Engineering, 2018)
To simulate the bending behavior of wheat straw, a flexible straw model was developed based on the Hertz-Mindlin with bonding model using discrete element method. The proposed model was constructed by bonding straw units (filled by multi-spherical method) through parallel bonding keys. By means of a three-point bending test, single-factor sensitivity analysis and calibration of bonding parameters were performed. Results showed that elastic modulus of the flexible straw enhanced with the increase of bonded disk radius, normal stiffness per unit area and shear stiffness per unit area. The three bonding parameters were respectively calibrated to be 2.11 mm, 9.48×109 N/m3 and 4.67×109 N/m3 by solving the regression equation developed from Box-Behnken design. The simulated elastic modulus (in terms of those three calibrated parameters) exhibited 4.20% difference with the measured one. It proved that the flexible straw could accurately demonstrate bending property of the wheat straw. This would not only help to improve accuracy in simulating wheat straw, but also provide references for flexible straw modeling and parameters calibration of other crops.Keywords: DEM, flexible straw, three-point bending test, bonding parameters, sensitivity analysis, parameters calibrationDOI: 10.25165/j.ijabe.20181103.3381Citation: Liu F Y, Zhang J, Chen J. Modeling of flexible wheat straw by discrete element method and its parameters calibration. Int J Agric & Biol Eng, 2018; 11(3): 42–46.